Thermal and dielectric behaviour of fine-grained soils. Issue 2 (21st March 2016) - Hailemariam, Henok; Shrestha, Dinesh; Wuttke, Frank; Wagner, Norman
Abstract : The thermal conductivity and complex dielectric permittivity of soil are highly correlated and are both affected by the changes in chemical composition, grain structure and soil hydromechanical conditions. In this study, the relationship between thermal conductivity and complex dielectric permittivity of three fine-grained soils, with known chemical and hydromechanical properties, was theoretically and experimentally analysed using transient and high-frequency electromagnetic measurement techniques respectively. As expected, a strong correlation between thermal conductivity and complex dielectric permittivity of the studied soils was obtained for a wide range of soil saturation. Furthermore, a theoretical prediction model for the thermal conductivity of fine-grained soils based on the measurement of dielectric permittivity is proposed. Unlike most thermal conductivity prediction models, the new model, developed based on the Johansen model and the advanced Lichtenecker and Rother model, does not require moisture content as an input parameter thus providing the opportunity to obtain accurate estimation of thermal conductivity both on site and in the laboratory using dielectric measurement techniques such as an open-ended coaxial line method, avoiding soil disturbance or the need to extract samples for moisture content measurement.